Evaluation of Selection of Finite Element Model for Beam Analysis Based on Shear Stress Distribution - Mikhail V. Mozgolov; Galina E. Okolnikova (Structural Mechanics of Engineering Constructions and Buildings)
When analyzing building structures in software packages based on the finite element method, incorrect results can be obtained. To justify the correctness of the obtained solution, it is necessary to perform verification studies and engineering assessment of the obtained data. This is required by the national standard of Russian Federation on modeling. The correctness of constructing calculation models can be assessed by comparing the data of the finite element method with the reference value. A numerical experiment was carried out in the SCAD++ version 21 software package for five finite element models of a cantilever beam made of B15 grade concrete, with dimensions of 2.5×0.5×0.5 m: four solid models No. 1-4 and one “reference” model consisting of a dense grid of second-order volumetric finite elements of cubic shape. Based on the calculation results, a comparative analysis of the shear stress distribution pattern from shear force was performed for all models with stresses calculated using the well-known analytical method, according to the Zhuravskii formula. It was found that the shear stress distribution in the sections of four computer models No. 1-4 does not correspond to the theoretical values calculated according to the rules of strength of materials. An accurate solution can be obtained using the “reference” solid model proposed by the authors, consisting of a dense grid of volumetric finite elements of the second order of cubic shape.